Advances in understanding allelopathic interactions between weeds and crops - Eroğlu, Çağla Görkem (Burleigh Dodds Series in Agricultural Science, 2022)
This chapter focuses on advances in understanding allelopathic interactions between weeds and crops. In the first part, we discuss allelopathy in crop-weed interactions while the second part focuses on practical aspects of allelopathy with reference to IWM. The first part includes a detailed discussion on research findings on buckwheat (Fagopyrum esculentum) as our research group has studied its potential allelopathic properties during the last 10 years.